Forty-Three-Year-Old Female with Dopamine Secreting Pheochromocytoma of the Adrenal Gland - Tyler Haden; Marcin Zuberek; Naveen Pokala (Case Reports in Urology)
We report on a 43-year-old, asymptomatic female who presented with incidental finding of left adrenal mass. MRI gave concerns for possible pheochromocytoma but markers for pheochromocytoma were not elevated as expected. 24-hour urine dopamine levels (6988 μg/day) were significantly elevated. The patient successfully underwent robotic assisted radical left adrenalectomy and was diagnosed with a dopamine secreting pheochromocytoma. Pathology revealed increased malignant potential associated with the tumor. The patient underwent full metastatic workup, which was negative. At two years of follow-up there was no recurrence and normalization of lab values.